2012
DOI: 10.1177/2047487312451253
|View full text |Cite|
|
Sign up to set email alerts
|

Adherence to guidelines for the prescribing of double and triple combinations of antithrombotic agents

Abstract: There is room to further develop adherence to guideline-based prescribing of antithrombotic combination therapies and to improve prescription of gastric protection for patients receiving these high-risk combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…These recommendations involve the risk of the patient or healthcare providers overlooking that one of the TARs should be stopped. Our results suggest that erroneous DAPT continuation contributes substantially to guideline non-adherence in primary care, a conclusion that supports the findings of Warlé-van Herwaarden et al 16 DAPT is most frequently initiated in the hospital, for example, after a myocardial infarction or a cerebrovascular accident. This treatment is continued after discharge and should be stopped in the outpatient setting.…”
Section: -20supporting
confidence: 90%
See 2 more Smart Citations
“…These recommendations involve the risk of the patient or healthcare providers overlooking that one of the TARs should be stopped. Our results suggest that erroneous DAPT continuation contributes substantially to guideline non-adherence in primary care, a conclusion that supports the findings of Warlé-van Herwaarden et al 16 DAPT is most frequently initiated in the hospital, for example, after a myocardial infarction or a cerebrovascular accident. This treatment is continued after discharge and should be stopped in the outpatient setting.…”
Section: -20supporting
confidence: 90%
“…These results are in line with the findings of Warlé-van Herwaarden et al, who stated that 24% of patients from a community pharmacy who used DAPT had a deviation from the guidelines. 16 In the study by Warlé-van Herwaarden et al, the prescriber was not contacted, and it was therefore unknown whether the deviations were intentional or erroneous. In the present study, three of the eight patients with an erroneous deviation from the guidelines never had an indication for DAPT, while in five patients one of the two agents should have been stopped in the past.…”
Section: -20mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the guideline adherence in patients using antithrombotic medication [16][17][18][19]. Proietti et al and Lip et al found that in patients with atrial fibrillation, 40.9-60.6% received adequate antithrombotic treatment, 6.8-21.7% were overtreated and 52.3-17.3% were undertreated and received no antithrombotic treatment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…5 The expanding complexity of haemostaseology results in high demands on the physician in charge: multimorbidity of older patients and the new diversity of options for OAC available by novel anticoagulant drugs necessitate a careful consideration of benefits and risks of the treatment. 6 The cost pressure on the healthcare system requires an economical use of medical resources. 7 Major efforts are indispensable to provide further scientific evidence to cope with these clinical challenges.…”
Section: Introductionmentioning
confidence: 99%